Terrorism, Political Opinions, and Election Outcomes: Evidence from Europe - Giovanni Peri; Daniel I. Rees; Brock Smith (Institute of Labor Economics (IZA), 2020)
There is surprisingly little evidence on how terror attacks impact elections. With only a few exceptions, previous studies in this literature have focused on a particular country or attack, limiting their generalizability. Ours is the first comprehensive, multi-country examination of the effects of terror attacks on political opinions and election outcomes. The results provide little evidence that terror attacks are systematically related to Europeans' attitudes towards immigrants and how much trust they have in government. International terror attacks are, however, associated with an increase in the vote share received by nationalistic parties in Europe. These results are relevant to the ongoing debate among academics over the effectiveness of terror attacks.
Keywords: D72; D74; 330; terrorism; elections; nationalism; terror attack